Health Impact Assessment of Cyclone Bejisa in Reunion Island (France) Using Syndromic Surveillance. Issue 2 (27th February 2015) - Vilain, Pascal; Pagès, Frédéric; Combes, Xavier; Marianne Dit Cassou, Pierre-Jean; Mougin-Damour, Katia; Jacques-Antoine, Yves; Filleul, Laurent
Abstract: Introduction: On January 2, 2014, Cyclone Bejisa struck Reunion Island (France). This storm led to major material damages, such as power outages, disturbance of drinking water systems, road closures, and the evacuation of residents. In this context, the Regional Office of French Institute for Public Health Surveillance in Indian Ocean (Cire OI) set up an epidemiological surveillance in order to describe short-term health effects of the cyclone. Methods: The assessment of the health impact was based mainly on a syndromic surveillance system, including the activity of all emergency departments (EDs) and the Emergency Medical Service (EMS) of the island. From these data, several health indicators were collected and analyzed daily and weekly. To complete this assessment, all medical charts recorded in the EDs of Reunion Island from January 2, 2014 through January 5, 2014 were reviewed in order to identify visits directly and indirectly related to the cyclone, and to determine mechanisms of injuries. Results: The number of calls to the EMS peaked the day of the cyclone, and the number of ED visits increased markedly over the next two days. At the same time, a significant increase in visits for trauma, burns, and carbon monoxide poisoning was detected in all EDs. Among 1, 748 medical records reviewed, eight visits were directly related to the cyclone and 208 were indirectly related. For trauma, the main mechanisms of injury were falls and injuries by machinery or tools during the clean-up and repair works. Due to prolonged power outages, several patients were hospitalized: some to assure continuity of care, others to take care of an exacerbation of a chronic disease. An increase in leptospirosis cases linked to post-cyclone clean-up was observed two weeks after the cyclone. Conclusion: Information based on the syndromic surveillance system allowed the authors to assess rapidly the health impact of Cyclone Bejisa in Reunion Island; however, an underestimation of this impact was still possible. In the near future, several lines of work will be planned by the authors in order to improve the assessment. P Vilain, F Pagès, X Combes, PJ Marianne Dit Cassou, K Mougin-Damour, Y Jacques-Antoine, L Filleul .Health impact assessment of Cyclone Bejisa in Reunion Island (France) using syndromic surveillance .Prehosp Disaster Med .2015 ;30 (2 ):1 -8